Low-grade fibromyxoid sarcoma of the extremities: a clinicopathologic study of 24 cases and review of the literature - Sambri, Andrea; Righi, Alberto; Tuzzato, Gianmarco; Donati, Davide; Bianchi, Giuseppe (Polish Journal of Pathology, 2018)
Low-grade fibromyxoid sarcoma (LGFMS) and hybrid sclerosing epithelioid fibrosarcoma (SEF)/LGFMS have a low potential for recurrence (10%) and metastasis (5%) but they are notorious for late occurring metastases. The aim of this study was to evaluate the outcome of LGFMS and review similar cases reported in the literature. We retrospectively evaluated 24 LGFMS operated at a single Institution. All cases were histologically revised. Mean age was 34 years (range, 8 to 74). Two cases presented areas of SEF (hybrid tumours). Three patients presented with metastasis at diagnosis. A strong cytoplasmic staining for MUC4 antibody was found in the majority of neoplastic cells. RT-PCR was feasible in 6 cases and it detected the presence of FUS-CREB3L2 fusion gene chimeric transcript. Mean follow-up was 44 months (range, 6 to 217). Two patients developed lung metastasis after 9 and 26 months respectively. Low-grade fibromyxoid sarcoma has a various histopathologic spectrum with few cases of LGFMS that share histopathologic resemblance with SEF, thereby reinforcing a possibility of a link within these two. It is of paramount importance an accurate and extensive sampling and examination of the whole specimen, in order to identify higher risk patients.